Stevens–Johnson syndrome induced by Sintilimab: a case report and literature review - Kuang, Huan; Huang, DongBei; Hu, ChuXiang; Gong, LiPing; Yu, ZiYu; Zhu, XunJin; Lan, HongRong; Huang, Gang (Frontiers in Oncology, 2025)
BackgroundSkin diseases induced by Sintilimab, a programmed cell death protein-1 (PD-1) inhibitor, are rare, with only 28 cases reported. We provide a literature review on skin diseases associated with Sintilimab and summarize the patient’s primary disease, duration of Sintilimab use, treatment, and disease progression. This study aims to improve understanding of Stevens–Johnson syndrome (SJS) induced by this monoclonal antibody and its treatment strategies.Case descriptionWe report a case of SJS induced by Sintilimab in a patient treated at our hospital. The patient exhibited widespread erythema, papules, and vesicles, accompanied by mucosal erosion and exudation in the oral cavity, eyes, urethral orifice, and perianal region. The patient was immediately treated with intravenous methylprednisolone sodium succinate (40 mg/day), antihistamines, and supportive care, including fluid replacement and wound care. His symptoms gradually improved, and he was discharged after 20 days. At the 6-month follow-up, he remained stable, with no recurrence of symptoms.ConclusionsAlthough severe drug rash, including SJS, caused by PD-1 inhibitors is relatively uncommon, its underlying molecular pathogenesis remains unclear. Physicians should remain vigilant regarding potential adverse reactions when prescribing Sintilimab. If severe reactions occur, discontinuation of chemotherapy and immediate administration of adequate corticosteroids with symptomatic support can help reduce morbidity and mortality.